Literature analysis on product-service systems business model: a promising research field - Moro, Suzana Regina; Cauchick-Miguel, Paulo Augusto; Mendes, Glauco Henrique de Sousa (Brazilian Journal of Operations & Production Management, 2021)
Goal: Product-service system (PSS) is a business model implemented by organizations aiming at generating profitability and competitiveness, and contributing to sustainability. However, companies need to build up new skills to develop and implement PSS focused on business models that should be able to generate value. This context calls for a theoretical analysis with the objective of identifing characteristics of this type of business model by means of a literature review. Design/Methodology/Approach: A descriptive review was conducted, and 313 publications related to PSS business model were selected. A final set of 48 articles related to PSS and business models were identified as well as the number of publications per year and main journal. Mechanisms for generating value from the PSS business model and its components were described after content analysis. Results: Most of PSS business model publications were published in recent years with the main focus on sustainability. Fourteen business model components were identified from the literature to be considered when structuring a PSS, associated with value proposition, creation, delivery, and value capture mechanisms. The most common components were ‘value proposition’ and ‘key partners’, although their concepts need a clarification. The business model should be designed with a value-centric vision in an iterative process. Moreover, it must cover the interests of the entire PSS value network, considering environmental, economic, and social dimensions of sustainability. Limitation of the investigation: The analysis has not considered the related research field on servitization, and nor the publications related to the ‘value’ concept from interdisciplinary areas (e.g., marketing). Practical implications: Developing a PSS business model requires forming a value network, considering the interests and responsibilities of those involved for the generation of mutual value as well as the inter-organizational relationships. Originality/Value: As PSS as a business model is a promising field of study, this paper devotes more attention on developing this kind of business model.